2017
DOI: 10.18311/mvpjms/0/v0/i0/730
|View full text |Cite
|
Sign up to set email alerts
|

Study on Psychiatric Morbidity Among Young Patients of Acne Vulgaris at Tertiary Care Institute

Abstract: Background: Acne vulgaris is a skin condition occurs mainly in adolescents and young adults. It can affect an appearance of a person adversely. The impact of acne on the psychological well being has been the object of increasing attention in recent years. Most of the studies which have been conducted to identify the psychopathologies in patients with acne vulgaris have focused their attention on depression and anxiety. Aim: The aim of the present study was to identify sociodemographic profile and the psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…7,17,18 The rates of prevalence in the range of 41.7% to 93.3% have been reported in different countries with populations. 7,17,18 Ghadge et al 15 study found 35% were psychiatric morbidity. Another study Dadarwala et al 22 study found 81% were psychiatric morbidity.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…7,17,18 The rates of prevalence in the range of 41.7% to 93.3% have been reported in different countries with populations. 7,17,18 Ghadge et al 15 study found 35% were psychiatric morbidity. Another study Dadarwala et al 22 study found 81% were psychiatric morbidity.…”
Section: Methodsmentioning
confidence: 95%
“…Results: Table I associated with acne and it has a potential damage to the emotional functioning of some patients. 15 Clinically mild to moderate disease such as noncystic facial acne can be associated with significant depression & suicidal ideation. 5 Studies have also suggested that acne negatively affects quality of life as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation